Upaya Bidang Pemasaran Dinas Pariwisata Kota Ternate dalam Meningkatkan Kunjungan Wisatawan di Kota Ternate - Hikmatun Nazila Surahman; Betly Taghulihi; Fitria Soamole (Yayasan Literasi Sains Indonesia, 2023)
This writing aims to (1) To find out the efforts made by the Marketing Division of the Ternate City Tourism Office in increasing tourist visits in Ternate City (2) To find out the impact of marketing and promotions carried out by the Marketing Sector of the Ternate City Tourism Office. In this writing the author uses qualitative and quantitative methods. The benefits of this final assignment report for students are gaining experience and skills from the world of work and industry in accordance with the study program, Khairun University getting useful input for improving the curriculum in accordance with employment needs, and the Ternate City Tourism Office getting alternative prospective employees. Has been known for its quality and credibility. From the results of the discussion, to introduce Ternate City tourism, marketing and promotion of existing tourism must be carried out. Marketing and promotion are very important activities and must be carried out by the Ternate City Tourism Office to introduce and develop tourism in Ternate City. The data collection techniques used were observation, interviews, documentation and literature study. Data presentation uses interpretive descriptive techniques. These results show that the efforts made by the Marketing Sector of the Ternate City Tourism Office have had a very positive impact on tourist visits. To attract the attention of tourists, make tourists feel at home and want to return, it is recommended that the Marketing Division of the Ternate City Tourism Office develop activities at existing tourist attractions so that the videos or photos used for publications match reality to avoid tourist disappointment.